The effectiveness of multimedia learning on academic achievement in reproduction topic science subject - Teo, Yang Kiat; Jumintono, Jumintono; Kriswanto, Erwin Setyo; Sugiri, Sugiri; Etty Handayani, Etty Handayani; Yunita Anggarini, Yunita Anggarini; Mochamad Rofik, Mochamad Rofik (Horizon Research Publishing, 2020)
This study aims to evaluate the effectiveness of multimedia-based learning on the academic achievement of science subjects in junior high school students. The method used in this research is descriptive. This study involved 40 junior high school students in Malaysia. The research sample was divided into two groups, namely conventional (control) and experimental (based on multimedia). Data obtained by providing pre-test and post-test to students. Data collected were analysed using descriptive and inferential statistics. A normality test is performed to determine the distribution of data. Data were analysed with a 5% T-test. The results of the analysis on the pre-test scores indicate that students in conventional and experimental teaching have the same level of knowledge, whereas in the post-test scores there are significant differences between traditional teaching scores and multimedia teaching. The finding of this study also showed that the student-centered learning approach was suitable for learning science subjects for secondary education. Students were found more active in engaging themselves in their learning and contribute to higher academic achievement in the post-test result. In conclusion, the use of multimedia elements in learning materials enables students to learn at their own pace. Through learning with the integration of multimedia-mediated content, student achievement in science subjects is enhanced, and it has helped students to develop a better understanding of science concepts and ideas.